“It’s in my blood. It’s in my spirit. It’s in my ancestry”: Identity and its impact on Wellness for Métis Women, Two-Spirit, and Gender Diverse People in Victoria, British Columbia - Auger, Monique; Jones, Carly; Monchalin, Renée; Paul, Willow (First Peoples Child & Family Review, 2022)
This article illustrates perspectives on Métis cultural identity, belonging, and positionality, within the context of wellness. As authors, we have the privilege of sharing stories from 24 Métis women, Two-Spirit, and gender diverse people—living or accessing services on the unceded territory of the Lək’wəŋən-speaking peoples (in so-called Victoria, British Columbia). Their stories illustrate personal and intergenerational journeys of reclaiming Métis identity, while also highlighting the importance of culture, community, family, land, and location. As Métis researchers conducting Métis-specific research, we also share our own positionalities and reflect on our responsibilities to community and to the original caretakers of the land.